Fluorocarbon powder coating and preparation method thereof
By modifying the acrylic resin and mixing it with modified PMMA and PVDF fluorocarbon resin, using double-layer powder technology and modified PMMA as an adhesive aid, the challenges of fluorocarbon powder coatings in adhesion, weather resistance and UV resistance are solved, achieving efficient compatibility and bonding effects.
Patent Information
- Application Number
- CN202510359986.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-25
AI Technical Summary
Existing fluorocarbon powder coatings have challenges in improving adhesion and weather resistance, especially poor compatibility and insufficient UV resistance, resulting in poor performance when used in extreme climates.
The acrylic resin is modified by using materials such as methyl methacrylate, hydroxyethyl methacrylate, hexafluorobutyl methacrylate and methyl coumarate, and mixed with modified PMMA and PVDF fluorocarbon resin. The double-layer powder technology and modified PMMA are used as the binding aid to improve the compatibility and UV resistance of the coating.
It achieves the improvement of internal compatibility and UV resistance of fluorocarbon powder coating while maintaining the advantages of high weather resistance, and improves the bonding effect of the double-layer powder coating, avoiding the occurrence of layer separation.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder coatings, and in particular to a fluorocarbon powder coating and a preparation method thereof. Background Art
[0002] Fluorocarbon coating is a general term for a series of coatings with fluorine-containing resin as the main film-forming material. It is a new type of coating material modified and processed on the basis of fluorine resin. Its main feature is that the resin contains a large number of FC bonds, and its bond energy is 485kJmol -1 , high bond energy, so it shows super long weather resistance and chemical corrosion resistance. With global climate change, the demand for buildings and transportation facilities to withstand extreme climate conditions continues to increase, and super weather-resistant fluorocarbon coatings also have good market adaptability.
[0003] Although fluorocarbon resins have high weather resistance, such as PVDF (polyvinylidene fluoride) fluorocarbon resins, their own adhesion is very low and their compatibility is poor, which affects the overall mechanical properties. In order to solve this problem, the existing technology mainly modifies PVDF and introduces highly reactive functional groups into the molecular chain, such as the grafting method, which introduces one or more grafting monomers into the PVDF molecular chain. Although this improves the adhesion of the modified PVDF fluorocarbon resin powder coating, the high stability, oxidation resistance and weather resistance of the PVDF fluorocarbon resin itself are also significantly reduced, and the reaction is complex and difficult.
[0004] In addition, the adhesion of the coating can be improved by adding acrylic resin to the blend, but the anti-ultraviolet ability of acrylic resin is low and the weather resistance is poor. The addition of acrylic resin will affect the overall weather resistance, which will affect the anti-ultraviolet performance and weather resistance. In order to improve the anti-ultraviolet performance of acrylic resin, metal oxides are generally added as fillers, but the addition of metal oxides is likely to affect the overall compatibility effect. Therefore, how to make the added acrylic resin not affect the weather resistance while maintaining good compatibility and improving the anti-ultraviolet performance as much as possible is also a major problem at present.
[0005] In addition, with the global attention to environmental protection, various regions have introduced relevant policies to promote the use of low-VOC and environmentally friendly products, so powder coatings came into being. Powder coatings have no solvents, and the coatings are more environmentally friendly. The storage, transportation and use processes are also more convenient and cost-saving. However, the compatibility of the coatings is more difficult to grasp, and phase separation is prone to occur, especially PVDF fluorocarbon powder coatings. In addition, the current double-layer powder technology can improve the adhesion and weather resistance of the coating, but there has been no suitable bonding additive, resulting in poor bonding between layers. Over time, local layer separation, bubbles or cracks may also occur. Summary of the invention
[0006] In view of this, the present invention provides a fluorocarbon powder coating and a preparation method thereof, which can improve the internal compatibility and UV resistance while maintaining the advantage of high weather resistance, and improve the internal bonding effect of the double-layer powder.
[0007] In order to achieve the above object, the present invention provides a method for preparing a fluorocarbon powder coating, comprising the following steps: S1: premixing methyl methacrylate, hydroxyethyl methacrylate, hexafluorobutyl methacrylate, methyl p-coumarate and a solvent to obtain a premixed solution; S2: transferring the premixed liquid to a reaction kettle, heating it, adding an initiator, reacting it, filtering it, and drying it to obtain a modified acrylic resin; S3: uniformly mixing the modified acrylic resin and the filler, performing melt kneading, and extruding to obtain material A; S4: Put PVDF fluorocarbon resin and filler into a reaction kettle, heat up, stir to obtain material B, add material A and modified PMMA, mix evenly, cool and tablet to obtain powder coating; The modified PMMA is obtained by modifying PMMA with 2,2,3,3,3-pentafluoropropyl acrylate; The mass ratio of material A to material B is (2-3): (7-8); In the premixed liquid, the mass proportion of hexafluorobutyl methacrylate is 3-8%.
[0008] By adopting the above technical scheme, the modified acrylic resin obtained can not only improve its own anti-ultraviolet performance and weather resistance, but also improve the adhesion of fluorocarbon powder coatings; and by adopting double-layer powder technology, the film formed after coating is more inclined to accumulate a large amount of hydrophobic fluorocarbon resin layer (material B) with greater surface tension on the surface, and a large amount of modified acrylic resin layer (material A) with relatively smaller surface tension and greater viscosity is accumulated on the bottom, and modified PMMA is used as a bonding aid, which not only plays a bonding role but also can improve the compatibility of material A and material B, and better avoid the occurrence of layer separation.
[0009] By using methyl p-coumarate to modify acrylic resin, methyl p-coumarate has good antioxidant properties, can form resonance-stabilized phenol free radicals, absorb part of the energy in ultraviolet rays, and can capture and neutralize some free radicals when ultraviolet radiation generates some free radicals, thereby improving the anti-ultraviolet performance of acrylic resin. At the same time, methyl p-coumarate itself contains double bonds and ester groups, which are highly compatible with acrylic monomers, and can be free radical copolymerized to form random copolymers, which improves the anti-ultraviolet performance without causing compatibility problems. In addition, methyl p-coumarate is derived from bio-based lignin, which is environmentally friendly and easy to obtain. At the same time, hexafluorobutyl methacrylate is also introduced into acrylic resin. The introduction of CF bonds can improve the weather resistance of acrylic resin, but it is necessary to pay attention to the dosage, and its mass proportion should not exceed 8% to avoid affecting the viscosity and adhesion of acrylic resin.
[0010] By using 2,2,3,3,3-pentafluoropropyl acrylate to modify the bonding agent PMMA (polymethyl methacrylate), the chemical resistance is improved while the bonding strength between the PMMA bonding agent and the PVDF fluorocarbon resin layer is improved. The molecular chain of PVDF contains -CF2- groups, while 2,2,3,3,3-pentafluoropropyl acrylate contains pentafluoropropyl (-CF2CF2CF3) which has similar polarity to the fluorocarbon chain of PVDF. The pentafluoropropyl introduced into the PMMA chain segment through copolymerization modification can form a stronger intermolecular bonding force with PVDF through fluorine-fluorine interaction, effectively reducing phase separation. In addition, 2,2,3,3,3-pentafluoropropyl acrylate contains acrylate groups, which can be highly copolymerized with PMMA. The modified PMMA obtained can also maintain a high bonding effect with the acrylic resin layer. Therefore, the introduction of 2,2,3,3,3-pentafluoropropyl acrylate not only improves the chemical resistance of PMMA bonding additives, but also improves the bonding effect inside the double-layer powder coating, laying a solid foundation for the large-scale promotion and application of the double-layer powder coating market.
[0011] Preferably, the methyl p-coumarate is prepared by the following method: a. The raw material bagasse is washed and crushed, and lignin is extracted by Soxhlet extraction, and then alkaline hydrolysis is performed in a high pressure reactor, followed by acid precipitation and purification to obtain p-coumaric acid; b. Add thionyl chloride and DMF to the obtained p-coumaric acid, heat and stir to react until the solid is completely dissolved, and distill under reduced pressure to obtain p-coumaryl chloride, which is dissolved in methanol, placed in an ice bath, and methanol is added dropwise. The temperature is slowly raised to room temperature for reaction. After the reaction is completed, distill under reduced pressure, extract, and recrystallize to obtain methyl p-coumarate.
[0012] By adopting the above scheme, methyl p-coumarate can be extracted and prepared from waste bagasse, the raw materials are easily available, the preparation method is simple, and the anti-ultraviolet performance of the modified acrylic resin can be significantly improved.
[0013] Preferably, 3%wt sodium hydroxide and an antioxidant Na2SO3 are used for alkaline hydrolysis in a high-pressure reactor, and then 18%wt hydrochloric acid is used to adjust the pH to 2.2, and the mixture is allowed to stand for precipitation for 10-15h, centrifuged, and purified to obtain p-coumaric acid; In the step b, heating to 50-60°C, stirring and reacting for 3 hours until the solid is completely dissolved, distilling under reduced pressure to obtain p-coumaroyl chloride, dissolving in methanol, cooling to 0-5°C in an ice bath, then dropping methanol, slowly heating to room temperature and reacting for 5 hours; The molar ratio of p-coumaric acid to thionyl chloride, DMF and methanol is 1:1.3:0.1:5.
[0014] Preferably, the modified PMMA is prepared by the following method: MMA and 2,2,3,3,3-pentafluoropropyl acrylate are mixed evenly, tetrahydrofuran is added, and then an initiator is added, stirred until completely dissolved, nitrogen is passed for deoxygenation, the temperature is increased, the temperature is kept, a reaction is carried out, the temperature is lowered, methanol is added, filtering, washing, and vacuum drying are performed to obtain granular modified PMMA.
[0015] Preferably, the added mass of the 2,2,3,3,3-pentafluoropropyl acrylate accounts for 0.5-3% of the total mass of the modified PMMA.
[0016] The preparation method is simple and efficient, the amount of 2,2,3,3,3-pentafluoropropyl acrylate added is appropriate, and the use of tetrahydrofuran as a solvent can improve the dispersion effect of 2,2,3,3,3-pentafluoropropyl acrylate, so that the prepared modified PMMA has a better bonding effect.
[0017] Preferably, in the preparation process of the modified PMMA, azobisisobutyronitrile is added as an initiator, nitrogen is passed for 20 minutes for deoxygenation, the temperature is slowly raised to 60-65°C, kept warm for 1-2 hours, then raised to 75-80°C, reacted at a constant temperature for 6-8 hours, cooled to below 38°C, methanol is added, filtered, washed with methanol 2-4 times, and vacuum dried at 50°C for 24 hours to obtain granular modified PMMA.
[0018] Preferably, in step S2, the premixed liquid is transferred to a reactor, N2 is introduced to remove the air, the temperature is raised to 80-88°C, the initiator is slowly added dropwise, the temperature is kept for 4-6 hours, the temperature is lowered to 50-60°C, ammonia water as a neutralizing agent is added, the pH is adjusted to 7-8, unreacted impurities are removed by filtration, the mixture is dried, and crushed to obtain a modified acrylic resin.
[0019] Preferably, in the premixed solution, the mass proportion of methyl p-coumarate is 5-15%.
[0020] Preferably, in step S3, the modified acrylic resin, curing agent, surface smoothing agent and filler are uniformly mixed, melt-mixed and extruded by a melt extruder, and the temperature of zone I of the melt extruder is set to 105° C., and the temperature of zone II of the melt extruder is set to 95° C. This is a preferred temperature, and the temperature of zones I and II of the extruder can also be adjusted according to the proportion of the materials.
[0021] Preferably, in step S4, PVDF fluorocarbon resin and filler are placed in a reaction kettle, stirred for 15 minutes, heated to 95-120°C, kept warm and stirred for 10-20 minutes, the temperature is adjusted to 80-100°C, a surface lubricant and an accelerator are added, kept warm and stirred for 10-20 minutes to obtain material B, the temperature is adjusted to 60-80°C, material A and modified PMMA are added, kept warm and stirred for 20-40 minutes, fed into a feeder, mixed evenly, cooled and pressed into tablets, and multi-stage crushing is performed, and the nitrogen pressure is controlled to be 0.7MPa and the flow rate is 5-10m 2 / min, sieving to obtain powder particles with a particle size of 5-35 microns, and spheroidizing to obtain powder coating.
[0022] By adopting multi-stage crushing and controlling the nitrogen pressure to 0.7MPa and the flow rate to 5-10m 2 / min, thereby better controlling the particle size and distribution of the coating, increasing the filling density of the double-layer powder, improving the leveling property and enhancing the mixing effect.
[0023] Preferably, in step S1, the added solvent is one of propylene glycol methyl ether acetate, toluene and xylene.
[0024] Preferably, in step S2, the added initiator is azobisisobutyronitrile or benzoyl peroxide.
[0025] Preferably, the curing agent is one of self-sealed isophorone diisocyanate and caprolactam-sealed isophorone diisocyanate, the surface lubricant is polytetrafluoroethylene, the filler is one of nano-silicon dioxide and mica powder, and the accelerator is dibutyltin laurate.
[0026] The present invention also provides a fluorocarbon powder coating, which is prepared by the above-mentioned fluorocarbon powder coating preparation method, and the coating comprises the following components in parts by weight: 20-30 parts of PVDF fluorocarbon resin, 1-8 parts of curing agent, 5-30 parts of filler, 0.2-2 parts of surface smoothing agent, 0.5-5 parts of accelerator, 70-80 parts of modified acrylic resin, and 5-10 parts of modified PMMA; The modified acrylic resin includes the following raw materials in parts by weight: 40-65 parts of methyl methacrylate, 10-20 parts of butyl acrylate, 4-10 parts of hydroxyethyl methacrylate, 1-6 parts of hexafluorobutyl methacrylate, 3-10 parts of methyl p-coumarate, 70-100 parts of solvent, and 0.5-1 part of initiator; The modified PMMA comprises the following raw materials in parts by weight: 90-99 parts of MMA, 0.5-3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 50-100 parts of tetrahydrofuran, and 0.1-0.6 parts of initiator.
[0027] The above technical solution of the present invention includes at least the following beneficial effects: (1) The present invention uses methyl p-coumarate to modify acrylic resin. Methyl p-coumarate has good antioxidant properties and can form resonance-stabilized phenol free radicals, absorb part of the energy in ultraviolet rays, capture and neutralize free radicals, and thus improve the anti-ultraviolet performance of acrylic resin. At the same time, methyl p-coumarate itself contains double bonds and ester groups, which have a high degree of matching with acrylic ester monomers and can be free radical copolymerized to form random copolymers, thereby improving the anti-ultraviolet performance without causing compatibility problems. In addition, methyl p-coumarate is derived from bio-based lignin, which is environmentally friendly and easy to obtain.
[0028] (2) The present invention adopts double-layer powder technology to prepare powder coatings, so that the film formed after coating tends to accumulate a large amount of hydrophobic fluorocarbon resin layer (material B) with greater surface tension on the surface, and accumulates a large amount of modified acrylic resin layer (material A) with relatively smaller surface tension and greater viscosity on the bottom, and modified PMMA is used as a bonding aid, which not only plays a bonding role but also can improve the compatibility of material A and material B, thereby better avoiding the occurrence of layer separation.
[0029] (3) PMMA is modified by using 2,2,3,3,3-pentafluoropropyl acrylate. The pentafluoropropyl group (-CF2CF2CF3) contained in 2,2,3,3,3-pentafluoropropyl acrylate has similar polarity to the fluorocarbon chain of PVDF. The pentafluoropropyl group introduced into the PMMA chain segment by modified copolymerization can form a stronger intermolecular binding force with PVDF through fluorine-fluorine interaction, effectively reducing phase separation; and 2,2,3,3,3-pentafluoropropyl acrylate contains acrylate groups, which can be highly copolymerized with PMMA, and the modified PMMA obtained can also maintain a high degree of bonding with the acrylic resin layer. Therefore, the introduction of 2,2,3,3,3-pentafluoropropyl acrylate not only improves the chemical resistance of PMMA bonding aids, but also improves the bonding effect inside the double-layer powder coating, laying a solid foundation for the large-scale promotion and application of the double-layer powder coating market. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0031] The following is an example of the preparation of methyl p-coumarate.
[0032] Preparation Example 1 10 parts of bagasse as raw material were washed and crushed, and 50 parts of a mixed solvent of toluene and ethanol in a ratio of 2:1 were added to extract lignin for 6 hours by Soxhlet extraction method to remove fat-soluble impurities. 3%wt sodium hydroxide was added in a solid-liquid ratio of 1:15 (w / v), and 2 parts of Na2SO3 were added. Alkaline hydrolysis was carried out in a high-pressure reactor for 3 hours, and then 18%wt hydrochloric acid was used to adjust the pH to 2.2. The mixture was allowed to stand for precipitation for 10 hours, centrifuged, and purified to obtain p-coumaric acid. Then prepare the corresponding reagents according to the molar ratio of p-coumaric acid to thionyl chloride, DMF and methanol of 1:1.3:0.1:5, add thionyl chloride and DMF (N,N-dimethylformamide) to the obtained p-coumaric acid, heat to 50°C, stir and react for 3 hours until the solid is completely dissolved, remove the excess thionyl chloride by vacuum distillation to obtain p-coumaryl chloride, dissolve it in part of methanol, cool to 0°C in an ice bath, add the remaining methanol solution dropwise, slowly heat to room temperature and react for 5 hours, after the reaction is completed, remove methanol by vacuum distillation, extract with ethyl acetate, and recrystallize to obtain methyl p-coumarate.
[0033] Preparation Example 2 10 parts of bagasse as raw material were washed and crushed, and 60 parts of a mixed solvent of toluene and ethanol in a ratio of 2:1 were added to extract lignin for 6 hours by Soxhlet extraction method to remove fat-soluble impurities. 3%wt sodium hydroxide was added in a solid-liquid ratio of 1:15 (w / v), and 1.5 parts of Na2SO3 were added. Alkaline hydrolysis was carried out in a high-pressure reactor for 3 hours, and then 18%wt hydrochloric acid was used to adjust the pH to 2.2. The mixture was allowed to stand for precipitation for 15 hours, centrifuged, and purified to obtain p-coumaric acid. Then prepare the corresponding reagents according to the molar ratio of p-coumaric acid to thionyl chloride, DMF and methanol of 1:1.3:0.1:5, add thionyl chloride and DMF (N,N-dimethylformamide) to the obtained p-coumaric acid, heat to 60°C, stir and react for 3 hours until the solid is completely dissolved, remove the excess thionyl chloride by vacuum distillation to obtain p-coumaroyl chloride, dissolve it in part of methanol, cool to 5°C in an ice bath, add the remaining methanol solution dropwise, slowly heat to room temperature and react for 5 hours, after the reaction is completed, remove methanol by vacuum distillation, extract with ethyl acetate, recrystallize to obtain methyl p-coumarate.
[0034] Preparation Example 3 The only difference between this Preparation Example and Preparation Example 2 is that the precipitation is allowed to stand for 13 hours, thionyl chloride and DMF (N,N-dimethylformamide) are added to the obtained p-coumaric acid, heated to 58°C, and stirred for 3 hours until the solid is completely dissolved, and the excess thionyl chloride is removed by vacuum distillation to obtain p-coumaryl chloride, which is dissolved in part of methanol and cooled to 2°C in an ice bath. The other steps remain the same to prepare methyl p-coumarate.
[0035] In addition to being prepared locally using sugarcane waste residues, methyl p-coumarate can also be purchased directly. Its CAS number is 19367-38-5.
[0036] The following are examples of fluorocarbon powder coatings, wherein the CAS number of 2,2,3,3,3-pentafluoropropyl acrylate is 356-86-5, and the CAS number of MMA (hexafluorobutyl methacrylate) is 36405-47-7.
[0037] Example 1 65 parts of methyl methacrylate, 10 parts of butyl acrylate, 10 parts of hydroxyethyl methacrylate, 6 parts of hexafluorobutyl methacrylate and 10 parts of methyl p-coumarate were mixed evenly, 100 parts of propylene glycol methyl ether acetate were added as solvent, and stirred for 10 minutes to obtain a premixed solution; the premixed solution was then transferred to a reactor, N2 was introduced to remove the air, the temperature was raised to 88°C, 1 part of initiator benzoyl peroxide (BPO) was slowly added dropwise, and the temperature was kept for 6 hours. When the conversion rate was greater than 95%, the reaction was terminated, the temperature was lowered to 60°C, a neutralizing agent ammonia water was added, the pH was adjusted to 8, unreacted impurities were removed by filtration, and a transparent resin solution was obtained, which was dried and crushed to obtain a modified acrylic resin. Among them, methyl p-coumarate was prepared by Preparation Example 1.
[0038] Mix 99 parts of methyl methacrylate (MMA) and 3 parts of 2,2,3,3,3-pentafluoropropyl acrylate evenly, add 100 parts of tetrahydrofuran (THF), and then add 0.5 parts of initiator azobisisobutyronitrile (AIBN), stir until completely dissolved, pass nitrogen for 20 minutes to deoxygenate, slowly heat to 60°C, keep warm for 2 hours, then heat to 75°C, react at constant temperature for 8 hours, terminate the reaction when the conversion rate is greater than 95%, cool to below 38°C, add methanol to precipitate the polymer, filter, wash with methanol 4 times to remove unreacted monomers and solvent, and dry in vacuo at 50°C for 24 hours to obtain granular modified PMMA.
[0039] 80 parts of modified acrylic resin, 6 parts of self-sealed isophorone diisocyanate, 1.5 parts of polytetrafluoroethylene, and 20 parts of nano-silicon dioxide are mixed evenly, put into a melt extruder for melt mixing, evenly dispersed, then melt extruded, tableted, cooled, and finely crushed to obtain material A. 30 parts of PVDF fluorocarbon resin and 8 parts of nano-silicon dioxide are put into a reactor, stirred for 15 minutes, heated to 120°C, stirred for 10 minutes, adjusted to 100°C, added 0.5 parts of polytetrafluoroethylene and 5 parts of dibutyltin laurate, stirred for 10 minutes, adjusted to 80°C, added 10 parts of modified PMMA, and then added material A, stirred for 20 minutes, fed into a forced feeder, mixed evenly, cooled and tableted, cooled to room temperature, and multi-stage crushed, and the nitrogen pressure was controlled to 0.7MPa and the flow rate was 10m 2 / min, standard sieving, to obtain powder particles with a particle size of 5-35 microns, spheroidization treatment, to obtain powder coating.
[0040] Example 2 40 parts of methyl methacrylate, 20 parts of butyl acrylate, 6 parts of hydroxyethyl methacrylate, 3 parts of hexafluorobutyl methacrylate and 7 parts of methyl p-coumarate were mixed evenly, 70 parts of xylene solvent were added, and the mixture was stirred for 10 minutes to obtain a premixed solution; the premixed solution was then transferred to a reactor, N2 was introduced to remove the air, the temperature was raised to 80°C, 0.5 parts of initiator azobisisobutyronitrile (AIBN) was slowly added dropwise, and the temperature was kept for 4 hours. When the conversion rate was greater than 95%, the reaction was terminated, the temperature was lowered to 50°C, a neutralizing agent ammonia water was added, the pH was adjusted to 7, unreacted impurities were removed by filtration, and a transparent resin solution was obtained, which was dried and crushed to obtain a modified acrylic resin. Among them, methyl p-coumarate was prepared by Preparation Example 2.
[0041] Mix 90 parts of methyl methacrylate (MMA) and 0.5 parts of 2,2,3,3,3-pentafluoropropyl acrylate evenly, add 50-100 parts of tetrahydrofuran (THF), and then add 0.1 parts of initiator azobisisobutyronitrile (AIBN), stir until completely dissolved, pass nitrogen for 20 minutes to deoxygenate, slowly heat to 65°C, keep warm for 1 hour, then heat to 80°C, and react at constant temperature for 6 hours. When the conversion rate is greater than 95%, terminate the reaction, cool to below 38°C, add methanol to precipitate the polymer, filter, wash twice with methanol to remove unreacted monomers and solvent, and dry under vacuum at 50°C for 24 hours to obtain granular modified PMMA.
[0042] 70 parts of modified acrylic resin, 1 part of caprolactam-blocked isophorone diisocyanate, 0.1 part of polytetrafluoroethylene, and 3 parts of mica powder are mixed evenly, put into a melt extruder for melt mixing, evenly dispersed, then melt extruded, tableted, cooled, and finely crushed to obtain material A. 20 parts of PVDF fluorocarbon resin and 2 parts of filler mica powder are put into a reactor, stirred for 15 minutes, heated to 85°C, stirred for 20 minutes, adjusted to 100°C, added 0.1 parts of polytetrafluoroethylene and 1 part of dibutyltin laurate, stirred for 20 minutes, adjusted to 50°C, added 5 parts of modified PMMA, and then added material A, stirred for 40 minutes, fed into a forced feeder, mixed evenly, cooled and tableted, cooled to room temperature, and multi-stage crushed, and the nitrogen pressure was controlled to 0.7MPa and the flow rate was 5m 2 / min, standard sieving, to obtain powder particles with a particle size of 5-35 microns, spheroidization treatment, to obtain powder coating.
[0043] Example 3 50 parts of methyl methacrylate, 15 parts of butyl acrylate, 8 parts of hydroxyethyl methacrylate, 4 parts of hexafluorobutyl methacrylate and 8 parts of methyl p-coumarate were mixed evenly, 80 parts of toluene solvent were added, and the mixture was stirred for 10 minutes to obtain a premixed solution; the premixed solution was then transferred to a reactor, N2 was introduced to remove the air, the temperature was raised to 85°C, 0.6 parts of initiator azobisisobutyronitrile (AIBN) was slowly added dropwise, and the temperature was kept for 5 hours. When the conversion rate was greater than 95%, the reaction was terminated, the temperature was lowered to 55°C, a neutralizing agent ammonia water was added, the pH was adjusted to 8, unreacted impurities were removed by filtration, and a transparent resin solution was obtained, which was dried and crushed to obtain a modified acrylic resin. Among them, methyl p-coumarate was prepared by Preparation Example 3.
[0044] Mix 95 parts of methyl methacrylate (MMA) and 2 parts of 2,2,3,3,3-pentafluoropropyl acrylate evenly, add 90 parts of tetrahydrofuran (THF), and then add 0.3 parts of initiator azobisisobutyronitrile (AIBN), stir until completely dissolved, pass nitrogen for 20 minutes for deoxygenation, slowly heat to 60°C, keep warm for 1.5 hours, then heat to 76°C, and react at constant temperature for 6 hours. When the conversion rate is greater than 95%, terminate the reaction, cool to below 38°C, add methanol to precipitate the polymer, filter, wash with methanol 3 times to remove unreacted monomers and solvent, and dry in vacuo at 50°C for 24 hours to obtain granular modified PMMA.
[0045] 75 parts of modified acrylic resin, 5 parts of caprolactam-blocked isophorone diisocyanate, 0.6 parts of polytetrafluoroethylene, and 10 parts of nano-silicon dioxide were mixed evenly, put into a melt extruder for melt mixing, uniform dispersion, and then melt extrusion, tableting, cooling, and fine grinding to obtain material A. 25 parts of PVDF fluorocarbon resin and 3 parts of filler nano-silicon dioxide were put into a reactor, stirred for 15 minutes, heated to 110°C, stirred for 15 minutes, adjusted the temperature to 90°C, added 0.3 parts of polytetrafluoroethylene and 2 parts of dibutyltin laurate, stirred for 15 minutes, adjusted the temperature to 60°C, added 8 parts of modified PMMA, and then added material A, stirred for 30 minutes, fed into a forced feeder, mixed evenly, cooled and tableted, cooled to room temperature, and multi-stage crushing was performed, and the nitrogen pressure was controlled to 0.7MPa and the flow rate was 6m 2 / min, standard sieving, to obtain powder particles with a particle size of 5-35 microns, spheroidization treatment, to obtain powder coating.
[0046] Example 4 55 parts of methyl methacrylate, 15 parts of butyl acrylate, 8 parts of hydroxyethyl methacrylate, 3 parts of hexafluorobutyl methacrylate and 8 parts of methyl p-coumarate were mixed evenly, 80 parts of toluene solvent were added, and the mixture was stirred for 10 minutes to obtain a premixed solution; the premixed solution was then transferred to a reactor, N2 was introduced to remove the air, the temperature was raised to 85°C, 0.6 parts of azobisisobutyronitrile (AIBN) as an initiator was slowly added dropwise, and the temperature was kept for 5 hours. When the conversion rate was greater than 95%, the reaction was terminated, the temperature was lowered to 55°C, ammonia water as a neutralizing agent was added, the pH was adjusted to 8, unreacted impurities were removed by filtration, and a transparent resin solution was obtained, which was dried and crushed to obtain a modified acrylic resin. Among them, methyl p-coumarate was prepared by Preparation Example 3.
[0047] 96 parts of methyl methacrylate (MMA) and 2 parts of 2,2,3,3,3-pentafluoropropyl acrylate were mixed evenly, 90 parts of tetrahydrofuran (THF) were added, and then 0.3 parts of initiator azobisisobutyronitrile (AIBN) were added, and stirred until completely dissolved. Nitrogen was passed through for 20 minutes for deoxygenation, and the temperature was slowly raised to 60°C, kept warm for 1.5 hours, and then raised to 78°C. The reaction was kept at this temperature for 6 hours. When the conversion rate was greater than 95%, the reaction was terminated, the temperature was lowered to below 38°C, methanol was added to precipitate the polymer, filtered, washed with methanol 3 times to remove unreacted monomers and solvents, and dried under vacuum at 50°C for 24 hours to obtain granular modified PMMA.
[0048] 76 parts of modified acrylic resin, 5 parts of self-sealed isophorone diisocyanate, 0.6 parts of polytetrafluoroethylene, and 10 parts of nano-silicon dioxide were mixed evenly, put into a melt extruder for melt mixing, uniform dispersion, and then melt extrusion, tableting, cooling, and fine grinding to obtain material A. 25 parts of PVDF fluorocarbon resin and 3 parts of filler nano-silicon dioxide were put into a reactor, stirred for 15 minutes, heated to 110°C, stirred for 15 minutes, adjusted the temperature to 90°C, added 0.3 parts of polytetrafluoroethylene and 2 parts of dibutyltin laurate, stirred for 15 minutes, adjusted the temperature to 60°C, added 7 parts of modified PMMA, and then added material A, stirred for 30 minutes, fed into a forced feeder, mixed evenly, cooled and tableted, cooled to room temperature, and multi-stage crushing was performed, and the nitrogen pressure was controlled to 0.7MPa and the flow rate was 8m 2 / min, standard sieving, to obtain powder particles with a particle size of 5-35 microns, spheroidization treatment, to obtain powder coating.
[0049] Example 5 55 parts of methyl methacrylate, 12 parts of butyl acrylate, 8 parts of hydroxyethyl methacrylate, 2 parts of hexafluorobutyl methacrylate and 8 parts of methyl p-coumarate were mixed evenly, 80 parts of toluene solvent were added, and the mixture was stirred for 10 minutes to obtain a premixed solution; the premixed solution was then transferred to a reactor, N2 was introduced to remove the air, the temperature was raised to 85°C, 0.6 parts of initiator azobisisobutyronitrile (AIBN) was slowly added dropwise, and the temperature was kept for 5 hours. When the conversion rate was greater than 95%, the reaction was terminated, the temperature was lowered to 55°C, a neutralizing agent ammonia water was added, the pH was adjusted to 8, unreacted impurities were removed by filtration, and a transparent resin solution was obtained, which was dried and crushed to obtain a modified acrylic resin. Among them, methyl p-coumarate was prepared by Preparation Example 2.
[0050] 97 parts of methyl methacrylate (MMA) and 2 parts of 2,2,3,3,3-pentafluoropropyl acrylate were mixed evenly, 92 parts of tetrahydrofuran (THF) were added, and then 0.3 parts of initiator azobisisobutyronitrile (AIBN) were added, and stirred until completely dissolved. Nitrogen was passed through for 20 minutes for deoxygenation, and the temperature was slowly raised to 60°C, kept warm for 1.5 hours, and then raised to 78°C. The reaction was kept at this temperature for 6 hours. When the conversion rate was greater than 95%, the reaction was terminated, the temperature was lowered to below 38°C, methanol was added to precipitate the polymer, filtered, washed with methanol 3 times to remove unreacted monomers and solvents, and dried under vacuum at 50°C for 24 hours to obtain granular modified PMMA.
[0051] 75 parts of modified acrylic resin, 4 parts of self-sealed isophorone diisocyanate, 0.8 parts of polytetrafluoroethylene, and 10 parts of nano-silicon dioxide were mixed evenly, put into a melt extruder for melt mixing, uniform dispersion, and then melt extrusion, tableting, cooling, and fine grinding to obtain material A. 26 parts of PVDF fluorocarbon resin and 3 parts of filler nano-silicon dioxide were put into a reactor, stirred for 15 minutes, heated to 110°C, stirred for 15 minutes, adjusted the temperature to 93°C, added 0.3 parts of polytetrafluoroethylene and 2 parts of dibutyltin laurate, stirred for 15 minutes, adjusted the temperature to 60°C, added 8 parts of modified PMMA, and then added material A, stirred for 30 minutes, fed into a forced feeder, mixed evenly, cooled and tableted, cooled to room temperature, and multi-stage crushing was performed, and the nitrogen pressure was controlled to 0.7MPa and the flow rate was 6m 2 / min, standard sieving, to obtain powder particles with a particle size of 5-35 microns, spheroidization treatment, to obtain powder coating.
[0052] The present invention also carried out the following comparative examples and related tests Comparative Example 1 The only difference from Example 4 is that methyl methacrylate is used instead of methyl p-coumarate, that is, the amount of methyl methacrylate added in the process of preparing the modified acrylic resin is 63 parts, and the other components and preparation process are consistent with Example 4 to prepare a powder coating.
[0053] Comparative Example 2 The only difference from Example 4 is that conventional nano zinc oxide is used instead of methyl p-coumarate, and the other components and preparation process are the same as those of Example 4 to prepare a powder coating.
[0054] Comparative Example 3 The only difference from Example 4 is that modified PMMA is not prepared, but conventional PMMA is used instead. The other components and preparation process are the same as those of Example 4, and a powder coating is prepared.
[0055] Performance testing According to the following standards, the powder coatings obtained in Examples 1-5 and Comparative Examples 1-3 were tested for weather resistance, salt spray resistance, adhesion, hardness, UV resistance and antioxidant properties.
[0056] 1. Weather resistance test The test method is based on the standard GB / T 1865-2009, artificial weathering 1000H, irradiance: 0.51(W / m 2@340nm), BST: 65℃, temperature in the box: 38℃, humidity in the box: 50%RH, stage 1: light, 102min, stage 2: light, 18min, spray the front of the sample, total test time: 1000h; result requirements: color change ≤ level 2, gloss loss ≤ level 2, no abnormal phenomena such as powdering, bubbles, cracking, peeling, etc. The final summary of the test results is shown in Table 1 below.
[0057] (II) Salt spray resistance test The test method refers to the standard GB / T 10125-2021, and the salt spray resistance is tested for 900 hours. The intelligent salt spray corrosion test box is used, and the instrument number is E-033-011TD. The result requirements are: the scribe area: unidirectional corrosion ≤ 2.0mm, and the unscribe area: no abnormality. The final test results are summarized in Table 1 below.
[0058] Table 1
[0059] From the test results in Table 1 above, it can be clearly seen that the powder coating products obtained in Examples 1-5 prepared by the present invention have excellent artificial weathering resistance and salt spray resistance, and can meet the high weather resistance and salt spray resistance requirements of high-end buildings and ships.
[0060] From the test results of Comparative Examples 2-3, it can be seen that the powder coating obtained in Comparative Example 2 should be resistant to salt rust by adding metal oxides, but due to poor compatibility and poor adhesion, slight peeling occurs locally; the powder coating obtained in Comparative Example 3 cannot withstand long-term weather resistance and salt spray resistance tests due to insufficient binding force of the bonding additive, and is prone to local aging and stratification, slight blistering or even cracking, and cannot meet the requirements of high-performance coating products.
[0061] (III) Adhesion test The test method refers to the standard GB / T 9286-2021 for adhesion test, using the instrument coating adhesion tester, instrument number E-008-011TD, test conditions: (23±2)℃, (50±5)%, 16h, square grid, grid spacing 2mm, 6 grid lines in each direction, tape type 3M 600, tape peeling angle 60°, material type is hard; result requirement: ≤1 level. The final test results are summarized in Table 2 below.
[0062] (IV) Hardness (abrasion) test The test method refers to the standard GB / T 6739-2022 for hardness (scratch) test, and the fluorocarbon powder coating is tested before 1000h artificial weathering resistance and after 1000h artificial weathering resistance. The technical requirement is: hardness>1H. The final test results are summarized in Table 2 below.
[0063] (V) UV resistance test The test method refers to the standard GB / T 1865-2009, the test result evaluation standard is whether the color changes, and the technical requirement is: no color change. The final test results are summarized in Table 2 below.
[0064] (VI) Antioxidant test The test method is based on the standard GB / T 1766-2008. The test result evaluation standard is whether powdering occurs. The technical requirement is: no powdering. The final test results are summarized in Table 2 below.
[0065] Table 2
[0066] From the test results in Table 2 above, it can be clearly seen that the powder coating products obtained in Examples 1-5 prepared by the present invention have excellent adhesion, hardness, UV resistance and antioxidant properties, and can meet the requirements of high-performance powder coatings.
[0067] From the test results of Comparative Examples 1-2, it can be seen that although the powder coating obtained in Comparative Example 1 has excellent adhesion performance, its UV resistance and oxidation resistance are poor, and its hardness after aging also decreases, indicating that the modification of acrylic resin by methyl p-coumarate can significantly improve the UV resistance and oxidation resistance, and thus affect the long-term aging hardness performance. The powder coating of Comparative Example 2 can improve the UV resistance due to the addition of metal oxides, but its compatibility is poor, which will affect the adhesion of the product and cannot meet the requirements of high-performance coating products.
[0068] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a fluorocarbon powder coating, characterized in that: The following steps are involved: S1: premixing methyl methacrylate, hydroxyethyl methacrylate, hexafluorobutyl methacrylate, methyl p-coumarate and a solvent to obtain a premixed solution; S2: transferring the premixed liquid to a reaction kettle, heating it, adding an initiator, reacting it, filtering it, and drying it to obtain a modified acrylic resin; S3: uniformly mixing the modified acrylic resin and the filler, performing melt kneading, and extruding to obtain material A; S4: Put PVDF fluorocarbon resin and filler into a reaction kettle, heat up, stir to obtain material B, add material A and modified PMMA, mix evenly, cool and tablet to obtain powder coating; The modified PMMA is obtained by modifying PMMA with 2,2,3,3,3-pentafluoropropyl acrylate; The mass ratio of material A to material B is (2-3): (7-8); In the premixed liquid, the mass proportion of hexafluorobutyl methacrylate is 3-8%.
2. The method for preparing a fluorocarbon powder coating according to claim 1, characterized in that: The methyl p-coumarate is prepared by the following method: a. The raw material bagasse is washed and crushed, and lignin is extracted by Soxhlet extraction, and then alkaline hydrolysis is performed in a high pressure reactor, followed by acid precipitation and purification to obtain p-coumaric acid; b. Add thionyl chloride and DMF to the obtained p-coumaric acid, heat and stir to react until the solid is completely dissolved, and distill under reduced pressure to obtain p-coumaryl chloride, which is dissolved in methanol, placed in an ice bath, and methanol is added dropwise. The temperature is slowly raised to room temperature for reaction. After the reaction is completed, distill under reduced pressure, extract, and recrystallize to obtain methyl p-coumarate.
3. The method for preparing a fluorocarbon powder coating according to claim 2, characterized in that: In the step a, 3%wt sodium hydroxide and an antioxidant Na2SO3 are used to perform alkaline hydrolysis in a high-pressure reactor, and then 18%wt hydrochloric acid is used to adjust the pH to 2.2, and the mixture is allowed to stand for precipitation for 10-15h, centrifuged, and purified to obtain p-coumaric acid; In the step b, heating to 50-60°C, stirring and reacting for 3 hours until the solid is completely dissolved, distilling under reduced pressure to obtain p-coumaroyl chloride, dissolving in methanol, cooling to 0-5°C in an ice bath, then dropping methanol, slowly heating to room temperature and reacting for 5 hours; The molar ratio of p-coumaric acid to thionyl chloride, DMF and methanol is 1:1.3:0.1:
5.
4. The method for preparing a fluorocarbon powder coating according to claim 1, characterized in that: The modified PMMA is prepared by the following method: MMA and 2,2,3,3,3-pentafluoropropyl acrylate are uniformly mixed, tetrahydrofuran is added, and then an initiator is added, and the mixture is stirred until completely dissolved, nitrogen is passed through for deoxygenation, the mixture is heated, kept warm, reacted, cooled, methanol is added, filtered, washed, and vacuum dried to obtain granular modified PMMA; the mass of the added 2,2,3,3,3-pentafluoropropyl acrylate accounts for 0.5-3% of the mass of the total modified PMMA.
5. The method for preparing a fluorocarbon powder coating according to claim 4, characterized in that: In the preparation process of the modified PMMA, an initiator is added, azobisisobutyronitrile is passed through nitrogen for 20 minutes for deoxygenation, the temperature is slowly raised to 60-65°C, kept warm for 1-2 hours, then raised to 75-80°C, kept at a constant temperature for 6-8 hours, cooled to below 38°C, methanol is added, filtered, washed with methanol for 2-4 times, and vacuum dried at 50°C for 24 hours to obtain granular modified PMMA.
6. The method for preparing a fluorocarbon powder coating according to claim 1, characterized in that: In the step S2, the premixed liquid is transferred to a reactor, N2 is introduced to remove the air, the temperature is raised to 80-88°C, an initiator is slowly added dropwise, the temperature is kept for 4-6 hours, the temperature is lowered to 50-60°C, ammonia water as a neutralizing agent is added, the pH is adjusted to 7-8, the mixture is filtered, dried, and crushed to obtain a modified acrylic resin.
7. The method for preparing a fluorocarbon powder coating according to claim 1, characterized in that: In the step S3, the modified acrylic resin, the curing agent, the surface lubricant and the filler are uniformly mixed, and a melt extruder is used for melt mixing and extrusion. The temperature of the melt extruder zone I is set to 105° C., and the temperature of the melt extruder zone II is set to 95° C.; the curing agent is one of self-sealed isophorone diisocyanate and caprolactam-sealed isophorone diisocyanate, and the surface lubricant is polytetrafluoroethylene.
8. The method for preparing a fluorocarbon powder coating according to claim 1, characterized in that: In the step S4, PVDF fluorocarbon resin and filler are placed in a reaction kettle, stirred for 15 minutes, heated to 95-120°C, kept warm and stirred for 10-20 minutes, the temperature is adjusted to 80-100°C, a surface lubricant and an accelerator are added, kept warm and stirred for 10-20 minutes to obtain material B, the temperature is adjusted to 60-80°C, material A and modified PMMA are added, kept warm and stirred for 20-40 minutes, fed into a feeder, mixed evenly, cooled and tableted, multi-stage crushing is performed, and the nitrogen pressure is controlled to be 0.7MPa and the flow rate is 5-10m 2 / min, sieving to obtain powder particles with a particle size of 5-35 microns, and spheroidizing to obtain powder coating; the accelerator is dibutyltin laurate.
9. The method for preparing a fluorocarbon powder coating according to claim 1, characterized in that: The solvent added in step S1 is one of propylene glycol methyl ether acetate, toluene and xylene; in step S2, the initiator added is azobisisobutyronitrile or benzoyl peroxide; and the filler is one of nano-silicon dioxide and mica powder.
10. A fluorocarbon powder coating, characterized in that: The fluorocarbon powder coating is prepared by the preparation method of any one of claims 1 to 9, comprising the following components in parts by weight: 20-30 parts of PVDF fluorocarbon resin, 1-8 parts of curing agent, 5-30 parts of filler, 0.2-2 parts of surface smoothing agent, 0.5-5 parts of accelerator, 70-80 parts of modified acrylic resin, and 5-10 parts of modified PMMA; The modified acrylic resin includes the following raw materials in parts by weight: 40-65 parts of methyl methacrylate, 10-20 parts of butyl acrylate, 4-10 parts of hydroxyethyl methacrylate, 1-6 parts of hexafluorobutyl methacrylate, 3-10 parts of methyl p-coumarate, 70-100 parts of solvent, and 0.5-1 part of initiator; The modified PMMA comprises the following raw materials in parts by weight: 90-99 parts of MMA, 0.5-3 parts of 2,2,3,3,3-pentafluoropropyl acrylate, 50-100 parts of tetrahydrofuran, and 0.1-0.6 parts of initiator.
Citation Information
Patent Citations
Oxime ester photoinitiators
CN103998427A
Super-weather-resistant PVDF double-layer powder paint and preparation method thereof
CN108047836A
Method for preparing p-coumarate by catalyzing depolymerization of lignin through ionic liquid
CN114292185A
High-wear-resistance powder coating as well as preparation method and application thereof
CN118374210A
Preparation method of weather-resistant polyurethane resin and application of weather-resistant polyurethane resin in powder coating
CN118515842A